Relatório de Estágio Profissional "Uma passagem pelo mundo de um "mister" professor de Educação Física e a importância da relação com os alunos" - Lourenço Carlos Teixeira Nunes de Freitas (2018)
The internship report is a document developed following the Professional Internship and is part of the 2nd year of the Master's Program in Physical Education Teaching in Basic and Secondary Education of the Faculty of Sport of the University of Porto. The supervised teaching practice took place at Filipa de Vilhena Secondary School, located in Porto, where I had the opportunity to integrate a nucleus of internship consisting of three elements and assume the responsibility for the teaching of a 10th grade class. The internship report is based on a reflective process based on what the career of teaching during this year was, reporting lived experiences, acquired learnings and results achieved. Accordingly, this internship report is divided into five chapters: (1) Introduction; (2) Personal Dimension, in which the route taken up to now is introduced and reflected; (3) Teaching Practice Framework, where the professional internship is framed from an institutional, legal and functional point of view, together with the description of the teaching establishment and characterisation of the class, which was central to this process; (4) Achievement of the professional practice, which is divided into three main areas, where everything that has been done in practice during the year is reflected, as well as the participation in school and the relationship with the community, and the professional development, namely the research-action study. This study comes as a complement to the teaching practice, and the purpose is to understand the importance of the teacher-student relationship for the students' motivation in the Physical Education classes; (5) Conclusions and future perspectives, with the culmination of the whole school year and perspectives for the future, and finally, (6) Bibliographical References.